Above-ground phytomass and chemical composition dynamics of Stipeta Zalesskii phytocenosis in Ural-Ilek interfluves - Neilya V. Dusaeva; Olga G. Kalmykova; Gulnara Kh. Dusaeva (Acta Biologica Sibirica, 2022)
We carried our investigationsin one of the typical phytocenosesof the Trans-Volga-Kazakhstan herb bunchgrass steppes underprotected regime conditions. Forb-fescue-feather grass steppe community (Stipa zalesskii, S. lessingiana, Herbae stepposae) with Helictotrichon desertorum (Less.) Nevski and petrophytous elementswere considered as a model. The dynamics of the above-ground phytomass stocks of this community was on the “Burtinskaya steppe” site in the Orenburg State Nature Reserve using thesquare sample cut method. The content of the main macroelements N, K, Na, Ca, P, and Mg is determined. The Federal State Budgetary Institution and the State Agrochemical Service Center “Orenburgsky” conducted the analysis of the plant samples.The resultsobtained were compared with the available literary data. Statistical analysis using the nonparametric Mann-Whitney U-test (α=0.05) in Statistica 6.1 revealed significant differences in the content of some macroelements between the drought year 2015 and the wet year 2016. The share of cereals (dominant community Stipa zalesskii Wilensky, codominant S. lessingiana Trin. & Rupr.), both in living above-ground phytomass and in dead grass, have been prevailing. The following series of accumulation of elements: N>K>Na>Ca>P>Mg was common for both fractures in most reference periods. The above-ground phytomass stocks in the examined community ranged from 335 g/m² to 404 g/m² in 2015 and from 525 g/m² to 678 g/m² in 2016. The findings obtained complement the available data for grasslands and pastures, present the opportunity to assess them comparatively with reference to standard and steppe zones, and serve as the foundation for further monitoring.